Flipping the Undergraduate Economics Classroom: Using Online Videos to Enhance Teaching and Learning. (14th March 2016) - Caviglia‐Harris, Jill
Abstract : The flipped classroom has been proposed as a teaching method with the potential to enhance student learning by removing much of the ''transmission of knowledge'' from the classroom and replacing this with active learning approaches that enable the assimilation of information. This article analyzes the impact of a flipped undergraduate economics course that leverages an existing suite of online lectures by Khan Academy. The study employs a quasiexperimental design to evaluate the impact of two different flipped treatments on an undergraduate microeconomics principles final exam. Student achievement is compared for students in (i) a "traditional" undergraduate course; (ii) a "complemented" (or partially flipped) classroom including traditional "mini" lectures complemented with online video lectures assigned as homework; and (iii) a flipped classroom. Results suggest that students in both of the flipped courses scored between 4 and 14 percentage points higher on set of common questions and a cumulative final exam.